Circulating Pro-inflammatory Cytokines Do Not Explain Interindividual Variability in Visceral Sensitivity in Healthy Individuals - Pawlik, Robert J.; Petrakova, Liubov; Brotte, Lisa; Engler, Harald; Benson, Sven; Elsenbruch, Sigrid (Frontiers in Neuroscience, 2022)
A role of the immune system in the pathophysiology of pain and hyperalgesia has received growing attention, especially in the context of visceral pain and the gut-brain axis. While acute experimental inflammation is capable of inducing visceral hyperalgesia as part of sickness behaviour in healthy individuals, it remains unclear if normal plasma levels of circulating pro-inflammatory cytokines contribute to inter-individual variability in visceral sensitivity. We herein compiled data from a tightly-screened and well-characterized sample of healthy volunteers (N=98) allowing us to assess associations between visceral sensitivity and gastrointestinal symptoms, and plasma concentrations of three selected pro-inflammatory cytokines (i.e., TNF-alpha, IL-6, IL-8), along with cortisol and stress-related psychological variables. For analyses, we compared subgroups created to have distinct pro-inflammatory cytokine profiles, modelling healthy individuals at putative risk or resilience, respectively, for symptoms of the gut-brain axis, and compared them with respect to rectal sensory and pain thresholds and subclinical GI symptoms. Secondly, we computed multiple regression analyses to test if circulating pro-inflammatory markers predict visceral sensitivity in the whole sample. Despite pronounced subgroup differences in pro-inflammatory cytokine and cortisol concentrations, we observed no differences in measures of visceroception. In regression analyses, cytokines did not emerge as predictors. The pain threshold was predicted by emotional state and trait variables, especially state anxiety, together explaining 10.9% of the variance. These negative results do not support the hypothesis that systemic cytokine levels contribute to normal interindividual variability in visceroception in healthy individuals. Trajectories to visceral hyperalgesia as key markers in disorders of gut-brain interactions likely involve complex interactions of biological and psychological factors in keeping with a psychosocial model. Normal variations in systemic cytokines do not appear to constitute a vulnerability factor in otherwise healthy individuals, calling for prospective studies in at risk populations.